Risk Factors and Functional Outcomes with Early Neurological Deterioration after Mechanical Thrombectomy for Acute Large Vessel Occlusion Stroke - Liu, Hongwei; Zhang, Yi; Fan, Haixia; Wen, Chao (Journal of Neurological Surgery Part B: Skull Base, 2022)
Early neurological deterioration (END) is associated with a poor survival after mechanical thrombectomy (MT) in acute ischemic stroke (AIS). To assess risk factors and functional outcomes of END after MT in patients, we analyzed data from 79 patients who received MT with large-vessel occlusion. END after MT in patients is defined as an increase of two points or more in the National Institute of Health Stroke Scale (NIHSS) score, compared with the best neurological status within 7 days. The mechanism of END can be classified into: AIS progression, sICH, and encephaledema. A total of 32 AIS patients (40.5%) had END after MT. Risk factors for END after MT included: history of oral antiplatelet and/or anticoagulation drugs before MT (OR = 9.56,95% CI = 1.02–89.57), higher NIHSS score when admitted to hospital (OR = 1.24, 95% CI = 1.04–1.48), under the subtype of atherosclerotic stroke (OR = 17.36, 95% CI = 1.51–199.56), ASITN/SIR< 2 (OR = 15.78, 95% CI = 1.65–151.26), and prolonged period from AIS onset to the first revascularization (OR = 1.01, 95% CI = 1.00–1.02). AIS patients who had END at early stages were more likely to experience poor outcomes (Modified Rankin Scale [mRS] >2) at 90 days after MT (OR = 6.829, 95% CI = 1.573–29.655). Thus, AIS patients who had experienced END at early stages were more likely to have poor outcomes (mRS >2) at 90 days after MT, and the risk factors of END were connected to the mechanism of END.
Keywords: mechanical thrombectomy; acute ischemic stroke; early neurological deterioration; risk factors; mechanism